Tensile Strength Assessment of Palm Fruit Bunch and Corn Cob Particulates Hybrid Reinforced Aluminum-Based Composite - Chibuzo Ndubuisi Okoye; Paul Chukwulozie Okolie; Obiora Nnaemeka Ezenwa; John Chikaelo Okeke; Augustine Uzodinma Madumere; Nkechinyelu Ifeatu Ezeaku (Universitas Pahlawan Tuanku Tambusai, 2026)
Engineering and industrial requirements today, especially in the field of transportation, call for the development of advanced, light-weight materials with extremely high strength and performance. Recently, the increasing need to reduce energy consumption and pollution worldwide has pushed automobile industries and aerospace industries to search for lightweight materials while maintaining better performance (Kandpal et al., 2017; Mangai et al., 2023; Parveez et al., 2021). Tensile assessment of aluminium-based biocomposites containing different concentrations of palm fruit bunch (PFB) and corn cob (CCF) particles have been investigated using practical experiments.